A Long Way Coming: Designing Centralized Markets with Privately Informed Buyers and Sellers - Loertscher, Simon; Marx, Leslie M.; Wilkening, Tom (Journal of Economic Literature, 2015)
We discuss the economics literature relevant to the design of centralized two-sided market mechanisms for environments in which both buyers and sellers have private information. The existing literature and the history of spectrum auctions, including the incentive auction currently being designed by the FCC, can be employed to analyze such mechanisms. We compare the revenue– efficiency trade-off in an environment with private information on one side of the market versus the trade-off with private information on both sides of the market; we provide an impossibility theorem for the efficient allocation of goods using a deficit-free mechanism when there is private information on both sides of the market; we discuss practical deficit-free mechanisms for various environments with two-sided private information; and we provide a synthesis to guide market design efforts and related research going forward. (JEL D44, D47, D82, H82)